Control in Turkish - Oded, İlknur. (Thesis (M.A.)-Bogazici University. Institute of Social Sciences, 2006., 2006)
This study aims to investigate the properties of control in Turkish and provide a typology for Turkish control structures. To this end, the applicability of Hornstein's Movement Theory of Control (MTC) (1999), which treats control as an instance of NP movement, is investigated. To test the applicability of MTC, evidence is presented from split antecedents, co-indexation possibilities in adjunct clauses, the availability of partial control and implicit control, obligatory control under non c-command and Turkish raising structures. On the basis of this evidence, it is argued that control in Turkish cannot be treated as an instance of NP- movement. In view of the fact that MTC is not applicable to Turkish, Landau's proposal (1999), which preserves PRO account of GB to analyze control structures, is taken as a starting point for the analysis of Turkish control structures and a comprehensive typology of control is presented for Turkish. In this typology, the subtypes of Obligatory Control (OC) in Turkish are described. Along the lines of Landau (1999), it is proposed that the OC category in Turkish consists of two subtypes: EC (Exhaustive Control) and PC (Partial Control) and it is argued that complement in EC structures is tensed whereas it is tenseless in PC. With respect to NOC category, it is argued that NOC in Turkish consists of two subtypes, which are Logophoric Control and Arbitrary Control. In addition to OC and NOC categories, exceptional cases of OC are discussed as well.To conclude, compared to MTC, PRO account of control in GB provides us with a better basis for the analysis of Turkish control structures. This questions the applicability of Hornstein's MTC cross-linguistically.
Keywords: Control (Linguistics); Turkish language.